Variasi Kefalometri pada Beberapa Suku di Sumatera Barat - Rizia Irsa; - Syaifullah; Djong Hon Tjong (Universitas Andalas, 2013)
A study about cephalometry variations of three ethnic groups living in West Sumatra was conducted from May until August 2012. This study used survey method and purposive sampling technique. The measurements of cephalometry were taken from total of 150 individu samples with frontal photos from head-face. The result showed significant variations on head length, head width, upper facial height, bizygomatic breadth, eyes width, distance of endocathion, nose length, nose width, chin height, minimum frontal height and distance of stomion to menton. Based on statistic analysis, Nias, Minang and Mentawai ethnics showed different cephalic, facial, frontoparietal and nasalis type. Phenogram by UPGMA of three ethnic groups showed close relationship between Nias and Mentawai.Keywords : variation, cephalometry, ethnics, West Sumatra.